DAMPAK LINGKUNGAN EKSPLOITASI AIR TANAH DAN PEMBANGUNAN PABRIK AMDK PT. TIRTA INVESTAMA DI KAMPUNG SALAM, DESA DARMAGA DAN PASANGGRAHAN, KECAMATAN CISALAK, KABUPATEN SUBANG, JAWA BARAT - -, Achmad Sjafrudin (Fakultas Teknik Geologi Universitas Padjadjaran, 2009)
The ground water exploitation and the AMDK factory construction of PT. Investama at Darmaga and Pasawahan Village, Sub-District of Cisalak will raise effects towards the environment. Hence the needs of EIA study is very crucial to minimize all the effects that will appear in the future to support sustainable development.